WHAT ISN’T NEW IN THE NEW NORMAL: A FEMINIST ETHICAL PERSPECTIVE ON COVID-19 - Gilson, Erinn (Les ateliers de l'éthique / The Ethics Forum, 2021)
This essay argues that dominant responses to the COVID-19 pandemic redouble disparities in vulnerability to harms because these responses simply attempt to return to conditions prior to the outbreak of the virus. Although the widespread impact of COVID-19 has made interdependence more vivid, the underlying sociocultural devaluation of vulnerability, relationality, and dependency has intensified structural inequalities. People who were already disempowered and disadvantaged have been consigned to even more precarious conditions. A feminist ethical perspective avows vulnerability, relationality, and dependency as conditions that are both unavoidable and central to life. Such a perspective thus provides insight into why some dominant responses to the virus are unjust and what more ethical and more socially just responses to the pandemic, which foster social health as well as physical health, might look like.